[BP.09.04] FEASIBILITY OF NEWLY PROPOSED ALGORITHMS TO ASSESS DIASTOLIC DYSFUNCTION IN HYPERTENSIVE PATIENTS. (September 2017) - Cesari, M.; Maiolino, G.; Seccia, M.T.; Rossi, G.P.
Abstract : Objective: Left ventricular diastolic dysfunction (DD) has been widely investigated in the last decades, but its prevalence is still under debate because its definition varies across studies. Two new classifications of DD have recently been proposed; however, their practical feasibility remain uncertain. Hence, we investigated if these classifications can be applied in the routine assessment of hypertensive patients (HT) with normal ejection fraction but with a high probability of DD because of a high rate of left ventricular hypertrophy and subclinical systolic dysfunction. Design and method: We performed Doppler echocardiography in 158 consecutive HT and in 64 control healthy subjects; we compared the classification of DD proposed by the American Society of Echocardiography (ASE) in 2009 and in 2016, and the Thoraxcenter (TXC) algorithm. Results: The grading of DD showed wide variation depending on the algorithm considered. Using ASE/EAE 2009, ASE/EACVI 2016 and TXC 2016 classifications it was possible to categorize, respectively, 65%, 78% and 85% of the whole cohort, in 87%, 97%, 95% of the healthy subjects and in 57%, 71%, 80% of the HT (Figure 1). Figure. No caption available. Hence, the ASE/EAE 2009 classification of DD did not allow to categorize 35% in the whole cohort and 43% in the HT. The ASE/EACVI 2016 classification strongly underestimated DD in subjects with normal ejection fraction, while overestimating DD grade I in patients with myocardial disease and normal ejection fraction. At variance, using the TXC algorithm only 15% of the whole cohort were overlooked, and the prevalence of DD resulted 42% in hypertensive patients and 5% in healthy subjects. Moreover, the DD was graded as 25% grade I, 12% grade II and 5% grade III in all HT patients, and as 32% grade I, 16% grade II and 5% grade III in HT patients with LVH. Conclusions: In a cohort of referred HT with a high prevalence of left ventricular hypertrophy the TXC algorithm not only resulted to be more widely applicable, but also provided a reasonable grading of DD in patients with arterial hypertension and normal ejection fraction.